WAWASAN BARU KAJIAN ASBĀB AL-NUZŪL : Analisis Terhadap Pemikiran M. Amin Abdullah - Muhammad Anshori (Institut Agama Islam Negeri (IAIN) Keiri, 2018)
This paper Examined one of the main themes in the Ulumul Qur’an study that is asbāb al-nuzūl. The Qur’an is a Divine kalam which was revealed to the Prophet Muhammad who lived in the midst of an Arab society that had its own traditions and culture. Because it could be said that the Qur’an is not born from a vacuum of culture, it was closely related to the surrounding environment. To know the circumstances in which the Qur’an was revealed, it is necessary to know asbāb al-nuzūl. In Ulumul Qur’an’s classic literature, the study of science was highly prioritized because it helped in understanding the verses of the Qur’an. One of the interesting figures in studying asbāb al-nuzūl is M. Amin Abdullah. He divides the term into two: asbāb al-nuzūl al-qadīm and asbāb al-nuzūl al-jadīd. The first term refers to classical clerical studies that are only oriented to the past as they are found in the books of Ulumul Qur’an. Asbāb al-nuzūl al-qadīm is considered incapable of explaining the problems of the present so there must be a study of asbāb al-nuzūl al-jadīd. This term is one form of contextual study of the verses of the Qur’an to be more relevant and able to answer the problem of the present. Although Amin Abdullah’s study has not been comprehensive but he has tried to develop a contemporary Qur’anic study with a new version. Between asbāb al-nuzūl al-qadīm and asbāb alnuzūl al-jadīd must be coupled simultaneously in order to create a complete understanding of the Qur’an.